Building consumer trust through live streaming: A study of fashion purchase behavior - Larasati, Suci; Aisyah, Mitra Riani; Habie, Riska Octavia; Rusdi, Wahyudi (Institute of Computer Science (IOCS), 2025)
In recent years, live streaming has emerged as a transformative force in the digital commerce landscape, particularly within the fashion industry. This study aims to analyze the effect of live streaming on consumer purchasing behavior, with trust as a mediating variable. This research uses a quantitative approach, with data collected through questionnaires distributed to 276 respondents in Gorontalo Province, who are active consumers in purchasing fashion products through live streaming services such as Shopee Live and TikTok Live. The analysis was carried out using SmartPLS 3 software to test the validity, reliability, and structural relationships between variables. The results reveal three key findings: (1) live streaming exerts a significant and positive direct influence on purchase decisions; (2) live streaming significantly enhances consumer trust; and (3) trust itself significantly predicts purchase decisions. These findings underscore the dual function of live streaming as both a transactional and relational tool in online shopping contexts. Theoretically, the study enriches the literature by integrating real-time interactive media into trust-based consumer behavior models. Practically, the findings offer strategic insights for digital marketers and e-commerce platforms seeking to optimize live streaming as a trust-building and conversion-enhancing mechanism. These findings strengthen previous literature and emphasize the importance of interaction quality in live streaming-based digital marketing strategies. This research provides strategic implications for fashion businesses to optimize live-streaming features in building customer trust.